Information Practices of University’s Civil Servants in Managing Family Archives for Asset Declarations - Rufaidah Farhah; Ike Iswary Lawanda (Buletin Al-Turas, 2023)
PurposeThis study aims to elaborate on the information practices carried out by university’s civil servants in managing and preparing family archives for asset declaration purposes by applying a theory of everyday information practices. This study uses McKenzie’s two-dimensional model which consists of Active Seeking, Active Scanning, Non-directed Monitoring, and By Proxy modes, along with the Connecting and Interacting phases in each mode. MethodThis study is a descriptive qualitative study and utilizes the data analysis method. Research data was collected through semi-structured online interviews. The informants were selected based on purposive sampling.  Results/FindingsThe results of this study indicate that only three modes of information practices were applied by the university’s civil servants for asset declaration purposes. The three modes are Active Seeking, Active Scanning, and By Proxy. ConclusionInformation practices for archive management are a part of daily life. It cannot be separated from context such as the type of archive and for what purpose. It is clear that archival study is related to information practices.